(3efJgi Ced GdCQjH Ydi eZfi GddHjHs - (3EHQGgje Hf CMeO Hf Ydj GdMUacj GHf GdefdG, GHf GdefdG,J (B1032 (3g` s ((3Ydi Hf HcQi GdMdGb GdOeTbi GdMfai GdeMjhi s)
(3ChdgG (B:s
(3GdHGH GdKGfi ef GdcJGH ai JaSjQ GdLedI hPcQ CbSGegG hCMcGegG s
(3BNQgG (B:s
(3bGd GdeUfa JZeOg Gddg HQMeJg hgPG BNQ eG JjSQ EjQGOg ai gPG GdJCdja s
(3GdfSNI eTJedI Ydi GdLRA GdKGfj hGdCNjQ abW ef GdcJGHs
(3GdfSNI efbhdI Yf fSNI GdeDdas
(3HgG fXGe GdJYbjHIs
(3ai ChdgG agQSJ ddehVhYGJ hhbajI hJedc s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdfMhs